Imaging and clinicopathologic characteristics in a contemporary cohort of younger women with newly diagnosed breast cancer. (2016) - Gillman, Jennifer; Batel, Jennifer; Chun, Jennifer; Schwartz, Shira; Moy, Linda; Schnabel, Freya
Abstract: Background: Younger women tend to have dense breasts and early detection of breast cancer in this population remains challenging. Although MRI is more sensitive than mammography, MRI is associated with a greater false positive rate. The purpose of this study is to evaluate the relationship of MR imaging and clinical characteristics in young women with breast cancer. Methods: The Breast Cancer Database at our medical center was queried for all women who had a mammogram and MRI from 2010–2014. Variables included demographics, risk factors, tumor characteristics, mammographic breast density (MBD), background parenchymal enhancement (BPE), and assessment of fibroglandular tissue (FGT) with contiguous MR images. Statistical analyses included Pearson's Chi Square Tests. Results: Of 1829 women, 111 (6%) were <40 years at the time of breast cancer diagnosis. When compared to women ≥40 years, younger women more often presented with palpable masses ( p <0.0001), a higher proportion of BRCA1 mutations ( p =0.02), stage II–III tumors ( p <0.0001), invasive ductal carcinomas ( p =0.006), HER2-positive tumors ( p =0.005) and higher Ki-67 scores ( p =0.02). Younger women had increased MBD ( p <0.0001) and increased FGT ( p <0.0001) when compared to older women, however, BPE was not significantly different ( p =0.70). Conclusions: Younger women had more palpable lesions and increased MBD and FGT. However, BPE was not significantly different between age groups. This suggests that BPE may not contribute to the increase in false positives associated with MRI in premenopausal women. These results underscore the importance of the clinical breast exam and breast self-awareness in young women who do not undergo routine screening. Microabstract: Younger women with breast cancer often present with palpable lesions and more advanced breast disease. Younger women tend to have increased breast density, but there is a dearth of literature on MRI characteristics in this population. Since younger women have increased breast density and are not routinely screened, improved monitoring with clinical breast exams and breast self-awareness may be important.